Comparativo de cuatro formulaciones de nutrición mineral en el rendimiento y calidad de tomate (Lycopersicon esculentum Mill.) Var. Rio Grande en sistema hidropónico en Trujillo, La Libertad. - Mora Cerna, Aldo Jairo (2013)
This research was conducted in hydroponics module of National University of Trujillo, from July 2012 to January 2013. Four formulations of mineral nutrition were compared in the production and quality of the tomato. (Licopersicon esculentum Mill) Var. Rio Grande in hydroponic system. The formulations evaluated were; T1 (Formulation of mineral nutrition in based on the recommended by “La Molina”), T2 (Formulation of mineral nutrition in based on the recommended by SQM), T3 (Formulation of mineral nutrition in based on the recommended by Rodriguez et al.) T4 (Formulation of mineral nutrition in based on the recommended by Lesur).Each formulation was composed of three Hydroponics nutrient solutions applied according to the phenological stage of the crop. The experiment was installed in a completely randomized design with 4 treatments and 4 replications. It was concluded that there is no statistically significant difference in plant height at any stage of the crop. With the treatment, T2, T4 and T3, the largest diameter of the stem is obtained in the vegetative and productive phase of the crop, being this difference statistically meaningful. It wasn´t found a meaningful difference in the number of days to harvest; just as the number of fruits per plant by cutting. It wasn´t found meaningful difference as for the number of fruits per plant. There is statistical difference relative to the weight of fruit per plant by cutting being the superior T1 with which was obtained 0,128 Kg versus 0,094 Kg; 0,087 Kg and 0,096 Kg obtained in the treatments T2, T3 and T4, respectively. With the T1, the highest valve with respect to the weight of the fruits per plant was obtained; 1,278 Kg being statistically superior to other treatments. There is significant difference to the production, being T1 statistically superior where it was obtained 24.35 t/ha versus treatments T4, T2, T3 which performances were 18,27 t/ha; 17,82t/ha ; 16,62t/ha, respectively. It was found statistical difference regarding the polar diameter of the fruit being T1 superior (5,095cm) regarding T3 and T4 where it was obtained 4,548cm, respectively. It wasn´t found statistical difference respect to the equatorial diameter of the fruit.